Trade in Risky Assets - Svensson, Lars E.O. (American Economic Review, 1987)
This paper developes a theory of the international trade pattern in risky assets by applying the law of comparative advantage to asset trade. According to this law there is a tendency for a country to import assets that have relatively high autarky prices. The Autarky price of an asset is high if the autarky real interest rate is low, or if the asset's autarky risk measure (the product of the risk premium and the asset price) is low. It is examined how autarky interest rates and risk measures are affected by international differences in (i) stochastic properties of output/endowments, (ii) the rate of time preference, (iii) the degree of risk aversion, and (iv) subjective beliefs, and how such differences predict overall capital account deficits or surpluses as well as the composition of the capital account into trade in arbitrary risky assets and the special cases of sure indexed bonds, stocks (claims to output), and Arrow-Debreu securities.